DIGESTIBILITY AND RETENTION OF NUTRIENTS OF BROILERS AT DIFFERENT DIETARY LEVELS OF DEOILED RICE BRAN (DORB) (Indian Journal of Animal Production and Management, 2014)
Two hundred ten day old commercial broiler chicks divided into seven groups (T0 - control, T1, T2, T3, T4, T5 and T6) of 30 chicks were allotted to four iso-nitrogenous dietary treatments, viz. D0, D1, D2 and D3, containing 0 (control), 10, 15 and 20 per cent of DORB for 6 weeks followed by a metabolic trial. T1, T2 and T3 groups were offered experimental diets –D1, D2 and D3 from 0-42 days and T4, T5 and T6 groups were offered from 22-42 days respectively. The average body weight gain, feed consumption and feed conversion ratios did not differ significantly (P>0.05) among the groups; however, the digestibility of CF was significantly (P0.05) lower at 20 per cent level of DORB inclusion irrespective of the stages of feeding.
Keywords: DORB; broilers; growth performance; digestibility; retention